PENERAPAN PEMBELAJARAN MELALUI KEGIATAN LABORATORIUM INKUIRI TERBIMBING UNTUK MENINGKATKAN KEMAMPUAN PEMECAHAN MASALAH, BERKOMUNIKASI, DAN BEKERJASAMA (UPEJ Unnes Physics Education Journal, 2013)
Guided-inquiry laboratory activity is one of learning strategies that can train students to have problem solving,communication, and cooperation skills. Guided inquiry laboratory activity teachers share responsibility for thestudent to investigate a problem in class. Teachers act as facilitators and providers problem.The purpose of thisresearch is to improve and to know the increase of problem solving, communication, and collaboration skills ofhigh school students with the application of learning through guided-inquiry laboratory activities. The researchdesign is Pretest-Posttest Control Group. The research results show that there is an increase in problem-solving,communication, and collaboration skills after applying learning through guided-inquiry laboratory activity.The obtained gain test results show there is an increase of problem solving, communication, and cooperationskills of control class, respectively for 0.3, 0,201; 0.31. While the experimental class is respectively at 0.65,0.304; 0.48. Test of significance shows that problem solving, communication, and cooperation skills ofexperiment class are better than the control class. Based on the analysis, it was found that the application oflearning through guided-inquiry laboratory activities can improve the problem solving, communication, andcollaboration skills.